A utilização do BIM na verificação da ABNT NBR 9050:2015 (norma de acessibilidade) na fase de desenvolvimento de projetos - Genova, Mariana Vaz de (2019)
The concepts related to accessibility have changed in recent decades, meeting not only the needs of people with disabilities, but of all people (universal design). The technical codes being of utmost importance to ensure accessibility in buildings, this paper aims to demonstrate the application of Building Information Modeling (BIM) in checking the Brazilian Code NBR9050:2015 during the project development phase. The research method adopted is the analytical one, consisting in the analysis of resources available on ArchiCAD along with the development of verification rules on Solibri Model Checker (SMC). These features and rules were tested on a single-family housing model developed on ArchiCAD, representing the project development process with simultaneous verification in a simplified form. Therefore, it was possible to verify the effectiveness of BIM in code checking, analyzing the results obtained in both programs. The research is expected to contribute to designers by automating accessibility checking in architectural designs, without the need for advanced programming knowledge by the professionals involved.